2002
DOI: 10.1148/radiol.2251010999
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Mammography and US in the Evaluation of a Palpable Abnormality: Retrospective Review

Abstract: A negative mammographic and US finding of a palpable abnormality does not exclude breast cancer, but the likelihood of breast cancer is low, approximately 2.6%-2.7%. It may be higher if the breast tissues are dense and lower if they are predominantly fatty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 12 publications
6
39
1
1
Order By: Relevance
“…Further, it was reassuring as reported by Moy et al [2] that the false negative rate could be reduced to 2.6% by the addition of ultrasound. Ultrasound is a relatively simple, noninvasive directed examination of the breast.…”
supporting
confidence: 54%
“…Further, it was reassuring as reported by Moy et al [2] that the false negative rate could be reduced to 2.6% by the addition of ultrasound. Ultrasound is a relatively simple, noninvasive directed examination of the breast.…”
supporting
confidence: 54%
“…The results of several studies [3,4,9,22,23] have demonstrated that the addition of ultrasound to mammography has raised the sensitivity of imaging in breast carcinoma to 94-97%. This in turn has resulted in debate as to the need to biopsy patients with normal mammography and normal ultrasound findings [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of mammography was impressively high in the detection of smaller cancers particularly in younger women (Baker, 1982). The likelihood of having breast cancer in negative mammography patients is low, approximately 2.6%-2.7% (Moy et al, 2002). A more recent report mentioned that the use of mammography results in a 25% to 30% decreased 3596 mortality rate in screened women compared with controls after 5 to 7 years (Ng and Muttarak, 2003).…”
Section: Practice and Barriers Of Mammography Among Malaysian Women Imentioning
confidence: 99%